2019
DOI: 10.1371/journal.pone.0221655
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hardness of cadmium telluride solar cells in proton therapy beam mode

Abstract: We evaluated the durability of cadmium telluride (CdTe) solar cells upon proton beam irradiation as well as the possibility of achieving a dosimeter usable in proton beam therapy by applying 100 MeV of pencil beam scanning (PBS) irradiation. Specifically, a 100 MeV proton PBS beam was applied at irradiation doses of 0, 1012, 1013, 1014, and 1015 cm-2. According to the results, the remaining factors (defined as the ratio of the degraded value to the initial value) of open-circuit voltage (Voc), short-circuit cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The second generation of cadmium telluride (CdTe) thin-film solar cells, combined with metal plates (e.g., copper), have sufficiently high atomic number and electron density to improve quantum efficiency. [17][18][19][20] Therefore, CdTe photovoltaic devices can detect radiation directly without conversion to visible light. CdTe detectors were found to be suitable for 6 MV X-ray measurements, as the percentage depth doses (PDDs) measured using CdTe detectors were in good agreement with the PDDs measured by ionization chambers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second generation of cadmium telluride (CdTe) thin-film solar cells, combined with metal plates (e.g., copper), have sufficiently high atomic number and electron density to improve quantum efficiency. [17][18][19][20] Therefore, CdTe photovoltaic devices can detect radiation directly without conversion to visible light. CdTe detectors were found to be suitable for 6 MV X-ray measurements, as the percentage depth doses (PDDs) measured using CdTe detectors were in good agreement with the PDDs measured by ionization chambers.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible thin‐film solar cells are types of semiconductor detectors that can be used in a simple setup because these cells do not require devices such as photomultiplier tubes. The second generation of cadmium telluride (CdTe) thin‐film solar cells, combined with metal plates (e.g., copper), have sufficiently high atomic number and electron density to improve quantum efficiency 17–20 . Therefore, CdTe photovoltaic devices can detect radiation directly without conversion to visible light.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, considering the increasing applications of CdTe-based cells, apart from efficiency, their long-term stability and applications in high-radiation environments, such as space missions, need to be assessed as well. Cho et al [13] fabricated a CdTe-based cell that can be utilized for space missions or beaminduced treatments and investigated the degradation process of the cell in a proton beam environment. Burst et al [14] showed that the hole density and carrier lifetime of CdTe can change when the sample is annealed in an environment containing Cd or Te vapor.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Recently, evaluation of the dose linearity, dose rate dependency, and field size dependency of organic solar cells and scintillators has suggested their potential utility in therapeutic radiation dosimetry. [27][28][29][30][31][32][33] Flexible thin film solar cells have advantages in radiation dosimetry applications, including their ability to be set up on curved surfaces and their cost-effectiveness. To date, two types of thin film solar cells have been considered useful for radiation dosimetry: cadmium telluride (CdTe) and amorphous silicon (a-Si).…”
Section: Introductionmentioning
confidence: 99%